(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The critical analyses of the various representations of the partition violence attempted in the preceding section clearly reveal in the obsessive nature of the event of vivisection of India in 1947. The event and the concomitant unprecedented carnage witnessed by the subcontinent came as a shockingly ironic reward of the united fight for freedom. The partition fiction, therefore, is a brutally realistic account of the blood curdling violence. However, it would be injudicious to infer that the partition novels considered in the study are mere stories of the harrowing incidents of violence. Instead, they are, in essence, discerning insights into the complex human nature. What Harish Raizada observes of Khushwant Singh is equally true of all other Indo-English novelists whose fiction has treated the holocaust of partition, Raijada writes that Khushwant Singh turned to fiction “to let out his disenchantment with the long-cherished human values in the wake of inhuman bestial horrors and insane savage killings on both sides during the partition of the sub-continent between India and Pakistan in August 1947....”